Learning language through task repetition - Bygate, Martin (Amsterdam ; Philadelphia : John Benjamins Publishing Company, 2018)
'After more than 20 years of research, this is the first book-length treatment of second language task repetition - the repetition of encounters with a task that involve re-using the same content with the same overall purpose. The topic links task performance with the growing mastery of both the task and of relevant language, and constitutes a site with special potential to promote learning within and across language lessons, and for preparing students for assessment and of course real-world language performance. The volume assembles chapters that complement each other in interesting ways: significant background reviews, studies of patterns of change across task repetition iterations, and reports on the use and nature of task repetition in language classes in on-going programmes. Contributors draw on a variety of interpretive frameworks and report from a range of language educational contexts. The volume will be of interest to language researchers, teacher educators, teachers, and students, as well as others interested in the contribution of task repetition to learning'--
Task repetition for language learning: a perspective from skill acquisition theory / Robert DeKeyser -- Grammatical structures and oral fluency in immediate task repetition: trigrams across repeated performances / Nel de Jong and Philip Tillman -- The effects of task repetition and task complexity on L2 lexicon use / YouJin Kim, Scott Crossley, YeonJoo Jung, Kristopher Kyle and Sanghee kang -- Discourse performance in L2 task repetition / Zhan Wang and Gaowei Chen -- The impact of intra-cultural and inter-cultural task repetition on interaction / Scott Aubrey -- Effects of task type, task-type repetition, and performance criteria on L2 oral production / Xingchao Hu -- The effects of awareness-raising through stimulated recall on the repeated performance of the same task and on a new task of the same type / Chris Sheppard and Rod Ellis -- Perform, reflect, recycle: enhancing task repetition in second language speaking classes / Tony Lynch -- Second language learning through repeated engagement in a poster presentation task / Emi Kobayashi and Masaki Kobayashi -- Mediating input-based tasks for beginner learners through task repetition: a sociocultural perspective / Natsuko Shintani -- Understanding benefits of repetition from a complex dynamic systems perspective: the case of a writing task / Ryo Nitta and Kyoko Baba -- Task repetition or task iteration? it does make a difference / Diane Larsen-Freeman.
Includes bibliographical references and index.
Keywords: Second language acquisition; English language -- Study and teaching -- Foreign speakers